The Use of Audiovisual Resources as a Learning Tool (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
The general objective of this research is to analyze the learning performance of students on the use of audiovisual resources. In order to fulfill that purpose, this research applied the experimental method from two randomly generated samples of the two groups (virtual classrooms) into which the enrolled students were administratively divided. The results obtained from the experiment show a significant improvement in the students’ learning performance. Finally, the students' perceptions about this didactic tool turned out to be very positive. The use of audiovisual resources in the classroom improves study habits and, consequently, a better academic performance is obtained.